Medical Informatics Education in Bosnia and Herzegovina - Masic, I. (Yearbook of Medical Informatics, 2004)
Medical informatics, as a separate medical discipline, is quickly developing in our country, both in Bosnia and Herzegovina. In our country, medical informatics has been a separate subject for the last ten years with regard to Medical curriculum at the biomedical faculties in Bosnia and Herzegovina. This is in accordance with the project of education related to the Bologna declaration and the project EURO MEDICINA. Last year, the Chair of Medical Informatics of the Medical Faculty in Sarajevo celebrated ten years of its existence.The research was performed using a separate questionnaire patterning data with defined characteristics for the quality assessment of the performed course. The total attitude of the assessed students shows dominant satisfaction with the majority of the parameters that are important for the assessment of the quality and the tuition contents which were evaluated through use of the questionnaire. Education in the field of medical informatics is based on the concept which is used in developed countries, according to the recommendations of the working groups of the European and international association of medical informatics. Theoretical and practical teaching and training performance as a whole is performed by use of the computer equipment, and the final knowledge check of the students is also performed using the Data Base Management System MSAccess specifically designed to cover full teaching and training material by using question sets in the data base which encircled nearly 1500 question combinations. In this paper, the author presents ten years of experience of medical informatics education at biomedical faculties in Bosnia and Herzegovina.